Seedling bank and ecological succession in a fragment of ciliary forest in lower São Francisco - Duarte, Juliana Maria Moreira; Ferreira, Robério Anastácio; Jesus, Janisson Batista de; Gama, Dráuzio Correia; Marroquim, Paula Maria Guimarães; Almeida, Ednei Santos de (Revista Ecologia e Nutrição Florestal - ENFLO, 2022)
The importance of evaluation of the seedling bank is to obtain the gathering of information on the natural regeneration of ecosystems. The objective of the study was to evaluate the seedling bank, identifying and analyzing the participation of the species involved in the natural succession process in a riparian forest fragment in the Sambambira Settlement, Santana do São Francisco, Sergipe State, Brazil. In three distinct environments (valley, slope and plateau background) were distributed, 25 plots with dimensions of 20 m x 20 m, in which they were installed small plots of 1 m². All individuals found with a minimum of 10 cm to a maximum of 100 cm high in the smalls plots were identified, quantified and measured. The phytosociological parameters and Shannon-Weaver (H’) and Pielou (J’) diversity rates were analyzed. Ecological groups were identified, as well as the effect of environments on the seedling bank by analysis of variance. 1,618 individuals were sampled, being found 117 morphospecies belonging to 24 families. The average monthly density was 16.18 seedlings m-². Rellia sp. and Pavonia cancellata were the species most abundant. The fragment presented high diversity of the regenerating stratum in initial process of secondary succession, indicating self-regenerating vegetation.